Organization of students’ research work in the conditions of providing professional orientation of the educational process - Alieksieieva, Ganna; Horbatiuk, Larysa; Kravchenko, Nataliya; Bohdan , Bohdan (Scientific notes of the pedagogical department, 2021)
The article considers the organization of research work of future engineers-teachers in the system of professional training of IT specialists through computer environment design. The contradictions between the usual system of training and the individual creative direction of the future professional activity of the specialist are analysed. The authors studied the concept of the computer environment, considered its information, software, and didactic component. The practical aspects of the organization of educational and research activities of future specialists, the specialty of which requires further research, in particular using the computer environment as an object of design, are revealed. Its intellectual properties are considered and it is proved that they are a reaction to human actions. The model of knowledge representation in the process of designing a computer environment is described and it is proved that the use of a network model in the form of a graph is the best to reflect the meaning of a holistic image. Thanks to the network model, the course in the discipline is created by a certain structure of modules, which consist of topics that contain tasks. This presentation of data is inherent in the semantic network, which is a combination of ideas and knowledge retention of the entire learning process in an individual educational trajectory. Thus, it is possible to adjust it depending on the level of effectiveness of the student's mastering the material. The informational, program and didactic components of the computer environment are substantiated, the basic requirements to the organization of research work of students from the point of view of designing where flexibility is the basic property of a system of management, in particular in questions of realization of various forms of occupations on professional training are revealed. An example of software implementation of a computer environment with an intuitive interface for working with information content is described. It is substantiated that the proposed principles of organization of research work can also be applied in the organization of research work of students of physical culture and sports profile.